Synthesis, Characterization and Thermal Analysis of Novel Methylene Bridged Bis-carbazole Based Bisbenzimidazoles - Mehmet Fatih Saglam (Hittite Journal of Science and Engineering, 2022)
The synthesis of novel bis(3-carbazoly1)methane linked bis-benzimidazoles is described. Construction of symmetrical bis-benzimidazoles on the bis-carbazolylmethane scaffold was succeeded by condensation reaction of benzene-1,2-diamine derivatives with bis(9-ethyl-9H-carbazole-3-carbaldehyde). The structural analysis of the targeted compounds 4-7 were confirmed by NMR, FT-IR spectroscopy and mass spectrometry. The thermal stability of final products 4-7 was also studied by thermogravimetric analysis (TGA).